Root starches enriched with proteins and phenolics from Pachyrhizus ahipa roots as gluten‐free ingredients for baked goods - Malgor, Martina (2020)
Ahipa is a gluten-free starchy root, bearing phenolics and a protein content of ~9% db. Ahipa proteins are hydrosoluble, thus they are lost during starch extraction. The aim of this work was to recover ahipa proteins by isoelectric point (pI) precipitation to enrich ahipa and cassava starches. Both enriched starches had protein contents of ~2%, and their ATR-FTIR spectra revealed bands characteristic of ahipa proteins. Enriched starches also contained phenolics in concentrations of 18-20 μg GAE/g. Enrichment lowered the whiteness index, but it remained higher than 90. Protein-enrichment did not modify gelatinization onset and peak temperatures but reduced the gelatinization enthalpy of ahipa starch. Enriched starches produced less-rigid buns than the native ones, with smaller and more homogeneously distributed alveoli in the crumb which resulted darker than the crust. Starch slurries acidified to the pI of ahipa proteins led to novel gluten-free ingredients by an easy, low cost process